Legal Analysis of Unlawful Acts in Corruption Crimes (Study of Decision Number 44/PID.SUS-TPK/2024/PN MDN) - Willem Cahyadi Halawa; Janpatar Simamora; Herlina Manullang (Journal of Legal and Cultural Analytics, 2025)
Legal accountability in corruption crimes is a legal consequence or liability that must be borne by the perpetrators of corruption crimes due to the losses they have caused. In the context of Indonesian law, corruption crimes are clearly regulated in Law Number 31 of 1999 concerning Corruption Crimes as amended by Law Number 20 of 2001 on the Eradication of Corruption Crimes (UU PTPK). In this writing, the author focuses on the forms of criminal liability in corruption crimes and acts against the law within corruption crimes, particularly in the case study of decision number 44/Pid.Sus-TPK/2024/PN Mdn. This study emphasizes a normative legal research method with a descriptive approach, where the research results aim to further examine the judicial considerations in deciding a case, particularly corruption cases.